Ecologia reprodutiva do periquito cara-suja Pyrrhura griseipectus no Maciço de Baturité, Ceará - Brasil - Nunes, Fábio de Paiva (2017)
We studied the reproduction of the Grey-breasted Parakeet (Pyrrhura griseipecuts) in Baturite Mountains, Ceará – Brazil. This critically endangered bird is a secondary cavity-nester, and in the study site it is reproducing both in natural and artificial nests. Reproductive data (number of eggs and nestlings) were collected from 2012 to 2016 to determine reproductive phases and seasonality. Ecological data was obtained in the 2016 to estimate the reproductive success of Grey-breasted parakeet (including feeding resources available surrounding the nest, temperature, humidity, presence of helpers and nest type (natural and nest-box) and compared to estimate the influence of environmental and behavioral variables on reproductive success. The Daily Survival Rate (DSR) was calculate with software MARK 8.2 and the estimation of the breeding success of Grey-breasted parakeet. A total of 116 nests were registered between the 2012 and 2016, with 786 eggs and 576 chicks. The reproductive success based on the period of 2016, were 41 active nests of Grey-breasted Parakeet were found, which 27 occurred in nest boxes and 14 in natural nests. The results showed that the reproductive calendar of the Grey-breasted Parakeet in the Baturité Mountains is positively correlated to rainfall (rs = 0.6696 and p < 0.0001). The success of the total nests was 75.6%. The Daily Survival Rate was 72.7%. The results showed that (i) the amount of resources in nests surrounds have an important role in the reproductive success of the Grey-breasted Parakeet; (ii) there is a positive influence of the helpers on the reproductive success of the Grey-breasted Parakeet in the Baturité Mountains and; (iii) the reproductive success of the the Grey-breasted Parakeet was higher in the nest boxes than in the natural nests. The results of this study showed the importance of available resources around nest sites and the efficiency of artificial nests to this endangered species.